Measurement of Fertility Benefits with Low Dose Thyroxine in Sub-fertile women - Pandit, Upendra; Banu, Farhat; Adhikari, Ayushma (Journal of Lumbini Medical College, 2017)
Introduction: High prevalence rate of thyroid dysfunction associated infertility is identified by a number of studies in Nepal. Thyroid dysfunction not only affects fertility but is also associated with miscarriage and fetal death. The objective of this study was to measure the fertility rate after low dose Thyroxine, 12.5 microgram, in women with subfertility. Methods: This was a descriptive and observational study done among women visiting infertility and in-vitro fertilization (IVF) center at Nepalgunj Medical College, Nepal. After undergoing baseline investigations for infertility, all women diagnosed with primary or secondary infertility were enrolled in the study. Male factor and tubal factor infertility was excluded. All 136 women who were enrolled in the study received 12.5 microgram of thyroxine supplementation for a period of three months and subsequently followed up until the same time period. Results: Out of 136 women, 83 (61.02%) women achieved pregnancy within three months of supplementation with low dose thyroxin. Among them, 34 (40.9%) women with primary infertility achieved pregnancy within three months. Similarly 14 (16.8%) women with previous miscarriage, 20 (24.09%) women with previous caesarean section within past five years back, and 15 (18.07%) with previous IUFD achieved pregnancy within three months. Conclusion: Low dose thyroxine supplementation would be beneficial and recommended to subfertile women of reproductive age group in the endemic regions of hypothyroidism. Dose adjustment would give extended benefits as soon as pregnancy is achieved. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, Page: 80-83 DOI: https://doi.org/10.22502/jlmc.v4i2.96